2012
DOI: 10.5812/ijhrba.4124
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Lifestyle Training in Relapse Prevention and Resiliency Enhancement for People with Substance Dependency

Abstract: The findings of the present study can provide for a permanent psychological treatment after detoxification and used in psychology intervention and deterrent from relapse prevention in people that are in detoxification stage.Background: Drug addiction is a complex disorder that incorporates multiple factors including those related to genetics, beliefs, unconscious processes, gender, and temperament as well as developmental, social, economic, and political factors. The present study investigates these factors. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The results showed that the combinative therapy, compared with MMT, was more effective in promoting resiliency. This finding is consistent with a part of the research results by Padesky and Mooney et al and Jafari et al ( 19 , 20 , 33 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results showed that the combinative therapy, compared with MMT, was more effective in promoting resiliency. This finding is consistent with a part of the research results by Padesky and Mooney et al and Jafari et al ( 19 , 20 , 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…Those are in the low-level resilience endpoint adapt themselves slightly to the new situations, recover from stressful situations to normal mode slowly ( 18 ). Jafari, in their study, concluded that the coping skills’ training is effective to increase the resilience and relapse prevention of the drug dependences ( 19 ). In this regard, the study of Padesky and Mooney as the basis of CBT showed that CBT leads to the development of clinical referrals’ positive features that one is to increase the resilience of referrals at the time of stress ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this questionnaire, the minimum score is 0 and the maximum score is 100, and the higher the person's score, the person is considered more resilient. 22 To score the CD-RIS, a score of 0 should be given for a completely incorrect item and a score of 4 for a completely correct item. This questionnaire does not utilize inverse scoring and no subscales are calculated for it.…”
Section: Methodsmentioning
confidence: 99%
“…situational characteristics), and the activity itself (i.e. structural characteristics) ( 3 , 4 ). Also, SA motivation, have been cited to include a desire for positive emotions and affective experiences, coping with negative emotional states, and as a means of social reinforcement ( 5 ).…”
Section: Backgroundsmentioning
confidence: 99%